Room temperature ferromagnetism in Fe-doped semiconductor ZrS2 single crystals. (27th April 2018) - Muhammad, Zahir; Lv, Haifeng; Wu, Chuanqiang; Habib, Muhammad; ur Rehman, Zia; Khan, Rashid; Chen, Shuangming; Wu, Xiaojun; Song, Li
Abstract: Two dimensional (2D) layered magnetic materials have obtained much attention due to their intriguing properties with a potential application in the field of spintronics. Herein, room-temperature ferromagnetism with 0.2 emu g −1 magnetic moment is realized in Fe-doped ZrS2 single crystals of millimeter size, in comparison with diamagnetic behaviour in ZrS2 . The electron paramagnetic resonance spectroscopy reveals that 5.2wt% Fe-doping ZrS2 crystal exhibit high spin value of g-factor about 3.57 at room temperature also confirmed this evidence, due to the unpaired electrons created by doped Fe atoms. First principle static electronic and magnetic calculations further confirm the increased stability of long range ferromagnetic ordering and enhanced magnetic moment in Fe-doped ZrS2, originating from the Fe spin polarized electron near the Fermi level.